World under Revision The Poetry of Wisława Szymborska - Ligeza, Wojciech (Cross-Roads, 2019)
This book provides a comprehensive overview of the entirety of Wisława Szymborska's poetic oeuvre. The author employs in-depth historical reflection on Szymborska's beginnings to reveal that - without describing her post-war beginnings and reflecting on her early entanglement in socialist realist newspeak - Szymborska's mature anti-dogmatic attitude will remain unclear. The book shows how Szymborska's rhetoric and stylistics - figures of reservation, negation, contradiction, tautology, and repetition - are closely connected with the construction of the poetic world and affect the shape of her messages. After all, Wisława Szymborska is a poet of sophisticated wit, a surprising freedom of expression, and an unusual game with various literary styles, even with colloquial Polish.